"The Four Pillars of Yoga: A Comprehensive Review of Asana, Pranayama, Meditation, and Surya Namaskar" (International Journal of Food and Nutritional Sciences, 2023)
This review paper provides an extensive exploration of the four fundamental elements of Yoga: Asana (postures), Pranayama (breathing techniques), Meditation, and Surya Namaskar (Sun Salutation). Each component is examined in detail to understand its unique contributions to the practice of Yoga and its impact on physical and mental well-being.